Transformasi Genetik Tembakau dengan Gen Cold Shock Protein melalui Perantara Agrobacterium tumefaciens - Seagames Waluyo; Sustiprijatno Sustiprijatno; Suharsono Suharsono (Jurnal AgroBiogen, 2013)
Coldshock protein (Csp) essential for organisms to survive inabiotic stress condition. CspB gene has been fused toubiquitin promoter in the T-DNA region of pCambia 1300int,and introduced into Agrobacterium tumefaciens LBA4404.This research had an objective to transform geneticallyNicotiana tabacum cv. Samsun by CspB gene under thecontrol of Ubiquitin promoter and NOS terminator mediatedby A. tumefaciens. Leaf discs were co-cultivated with A.tumefaciens LBA 4404. Based on the number of hygromycinresistantcalli, the efficiency of transformation was 57.5%. Inthe selective medium containing 50 μg/l hygromycin, theefficiency of regeneration of transgenic shoots was 82.6%.Based on PCR analysis using primers corresponding toubiquitin promoter and CspB gene, 18 putative tobaccotransgenic containing CspB gene under the control ofubiquitin promoter.